THE DEVELOPMENT OF MOBILE APPLICATION WITH CONNECTIVISM THEORY TO ENHANCE COMPUTING SCIENCE ABILITIES FOR GRADE 11 STUDENTS - Srisuphan , Ponpawee; Siripipattanakul, Sutithep; Diteeyont, Watsatree (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this research were: 1) To develop a mobile application with connectivism theory to enhance computing science abilities for grade 11 students. 2) To compare the pre-test and post-test of learning achievement with this mobile application to enhance computing science abilities. 3) To study the ability in the computing science of grade 11 students after using mobile application with connectivism theory. and 4) To study the students satisfaction towards learning with mobile application with connectivism theory to enhance computing science abilities. The sample group in this study was randomized 40 students in grade 11 by using the cluster random sampling from high school in the Triamudomsuknomklao Pathumthani school. The research tools: 1) mobile application 2) lesson plan 3) the pre-test and post-test 4) computing science abilities test and 5) the satisfaction questionnaires. The statistics for data analysis, including mean percentage, standard deviation, and t-test dependent sample. The research findings revealed: 1) mobile application with connectivism theory to enhance computing science abilities for grade 11 students that evaluated were a very good quality. 2) the learning achievement scores was significant higher than pre-test scores at .01 level. 3) the overview of students computing science abilities when studied with mobile application were at the very good quality and 4) students expressed the highest level of satisfaction with learning by using the mobile application.